Therapeutic vaccination using minimal HPV16 epitopes in a novel MHC-humanized murine HPV tumor model - Kruse, Sebastian; Büchler-Schäff, Marleen; Uhl, Philipp; Sauter, Max; Yang, Ruwen; Mier, Walter (OncoImmunology, 2019)
Therapeutic vaccination as a treatment option for HPV-induced cancers is actively pursued because the two HPV proteins E6 and E7 represent ideal targets for immunotherapy, as they are non-self and expressed in all tumor stages. MHC-humanized mice are valuable tools for the study of therapeutic cancer vaccines - given the availability of a suitable tumor model. Here, we present for the first time an HPV16 tumor model suitable for fully MHC-humanized A2.DR1 mice, PAP-A2 cells, which in contrast to existing HPV16 tumor models allows the exclusive study of HLA-A2- and DR1-mediated immune responses, without any interfering murine MHC-presented epitopes. We used several HPV16 epitopes that were shown to be presented on human cervical cancer cells by mass spectrometry for therapeutic anti-tumor vaccination in the new tumor model. All epitopes were immunogenic when rendered amphiphilic by incorporation into a molecule containing stearic acids. Prophylactic and therapeutic vaccination experiments with the epitope E7/11-19 demonstrated that effective immune responses could be induced with these vaccination approaches in A2.DR1 mice. Interestingly, the combination of E7/11-19 with other immunogenic HPV16 E6/E7 epitopes caused a reduction of vaccine efficacy, although all tested combinations resulted in a survival benefit. In summary, we present the first HPV16 tumor model for exclusive studies of HLA-A2-mediated anti-HPV tumor immune responses and show anti-tumor efficacy of minimal epitope vaccines.
Published online: 29 October 2018
Gesehen am /05.06.2019